2022
DOI: 10.1111/trf.16965
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia as a predictor of mortality and transfusion. A scoping review of hypocalcemia in trauma and hemostatic resuscitation

Abstract: Background Calcium plays an essential role in physiologic processes, including trauma's “Lethal Diamond.” Thus, inadequate serum calcium in trauma patients exacerbates the effects of hemorrhagic shock secondary to traumatic injury and subsequently poorer outcomes compared to those with adequate calcium levels. Evidence to date supports the consideration of calcium derangements when assessing the risk of mortality and the need for blood product transfusion in trauma patients. This review aims to further elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 21 publications
(52 reference statements)
0
20
0
1
Order By: Relevance
“…Hypocalcemia after pRBC transfusion is a well-known mechanism and calcium supplementation is included in resuscitation guidelines. Early calcium administration in trauma patients to prevent coagulopathy and reduce transfusion needs, on the contrary, still needs randomized prospective studies to support the causation between early hypocalcemia and coagulopathy itself [ 15 ]. Hypercalcemia as defined by ionized calcium > 1.3 resulted in 7 patients (0.9%) in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Hypocalcemia after pRBC transfusion is a well-known mechanism and calcium supplementation is included in resuscitation guidelines. Early calcium administration in trauma patients to prevent coagulopathy and reduce transfusion needs, on the contrary, still needs randomized prospective studies to support the causation between early hypocalcemia and coagulopathy itself [ 15 ]. Hypercalcemia as defined by ionized calcium > 1.3 resulted in 7 patients (0.9%) in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Hypocalcaemia should be corrected with calcium chloride in patients with significant bleeding to maintain coagulation according to the European Trauma Guidelines [39,40 ▪▪ ]. However, this recommendation is based on low-quality evidence, possibly driven by pathophysiological mechanisms at stake and multiple studies concluding that hypocalcaemia is associated with poor outcomes in critically injured patients [35,40 ▪▪ ,41]. Only one study has reported results of associations between outcome and calcium administration in major bleeding patients [40 ▪▪ ,42 ▪ ].…”
Section: Management Of Hypocalcaemia In the Icumentioning
confidence: 99%
“…With this focus on early administration of blood products, massive transfusion protocols (MTPs, commonly defined as transfusion of at least 10 U of blood in a 24-hr period) have become widely implemented (5). The Prevalence of hypocalcemia in the massively transfused population has become a well-described phenomenon (6)(7)(8)(9)(10)(11)(12). This is likely even more pronounced when using component therapy; compared with WB resuscitation, solely using component therapy typically results in transfusion of larger volumes of blood product (2,(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…More transfused products means more transfused citrate, which chelates free serum calcium and can worsen hypocalcemia. Retrospective studies have documented how hypocalcemia in massive transfusion is a risk factor for coagulopathy, death, additional transfusion requirements, increased ICU length of stay, ventilator days, need for emergent surgery, and even discharge destination (8,11,17,18). Some progress has been made; there is now an emphasis on measurement of ionized calcium (iCa) or total calcium/iCa ratio rather than total calcium alone (approximately 50% of circulating calcium biologically available) (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation